AN ANALYSIS OF INDEX, ICON, SYMBOL IN THE SONG OF IKAT AKU DI TULANG BELIKATMU: SAL PRIADI - Kemuning, Maudy Ariana; Sakinah, Myrna Nur (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2020)
This study aims to determine the types of icons, indexes, and symbols contained in the song